Growth of 48 built environment bacterial isolates on board the International Space Station (ISS) - Coil,David A.; Neches,Russell Y.; Lang,Jenna M.; Brown,Wendy E.; Severance,Mark; Cavalier,Darlene; Eisen,Jonathan A. (PeerJ, 2016)
Background. While significant attention has been paid to the potential risk of pathogenic microbes aboard crewed spacecraft, the non-pathogenic microbes in these habitats have received less consideration. Preliminary work has demonstrated that the interior of the International Space Station (ISS) has a microbial community resembling those of built environments on Earth. Here we report the results of sending 48 bacterial strains, collected from built environments on Earth, for a growth experiment on the ISS. This project was a component of Project MERCCURI (Microbial Ecology Research Combining Citizen and University Researchers on ISS). Results. Of the 48 strains sent to the ISS, 45 of them showed similar growth in space and on Earth using a relative growth measurement adapted for microgravity. The vast majority of species tested in this experiment have also been found in culture-independent surveys of the ISS. Only one bacterial strain showed significantly different growth in space. Bacillus safensis JPL-MERTA-8-2 grew 60% better in space than on Earth. Conclusions. The majority of bacteria tested were not affected by conditions aboard the ISS in this experiment (e.g., microgravity, cosmic radiation). Further work on Bacillus safensis could lead to interesting insights on why this strain grew so much better in space.
Keywords: Bacterial growth; International space station; Built environment; Microgravity; Space; Non-pathogenic